Soft-sediment deformation structures of mottled clay in Huizhou Quaternary basin, coastal South China - Chen, Zhen; Wang, Wen; Huang, Ping; Tang, Yongjie; Wang, Jing; Zeng, Qiang; Chen, Cong (Frontiers in Earth Science, 2023)
Tectonically induced liquefaction and the resulting soft-sediment deformation structure (SSDS) can provide useful information on paleo-earthquakes, which is vital for the assessment of geohazard susceptibility in tectonically active regions. In this study, we combined sedimentary and chronological methods to the reveal detailed characteristics of the mottled clay in the Huizhou Quaternary Basin. The dating results suggest that mottled clay usually developed during the late Pleistocene, overlying the fluvial deposit or embedding homogeneous aeolian yellow silt. Mottled clay has a typical bimodal frequency distribution with modal sizes at 5 and 80-90 μm, which are identical to those of the yellow silt and the underlying fluvial sand, respectively. Micro-X-ray fluorescence mapping revealed high concentrations of Fe and Si in the red and white fraction, respectively. In contrast, the red fraction of mottled clay has a high hematite content, similar to loess-like yellow silt, whereas the white fraction and the underlying fluvial sediments are dominated by goethite. This sedimentary evidence together suggests that the mottled clay could be an admixture of aeolian yellow silt and the underlying fluvial sand. Furthermore, diverse deformed structures (e.g., fragmented structures, sand veins, sand dykes and flame structures) were observed in mottled clay. Therefore, we suggest that the mottled clay structure in the Huizhou Basin is a product of liquefaction-induced SSDS. Tectonic activity was considered to have triggered the liquefaction and SSDS, which is supported by the close spatial relationship between the mottled clay and regional faults. We propose that the SSDS of mottled clay could be a potential indicator of paleo-earthquakes in the coastal Quaternary basins of the northern South China Sea.